Impacted denture in the left bronchus: aspiration in an awake state - Raj, Abhijit; Sebastian, Susan K.; Vijayan, Vikas (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Tracheobronchial foreign body aspiration is rare in adults. In adults it usually happens in a state of impaired alertness. We report a case of aspiration of a partial denture in an alert patient who presented with minimal symptoms. She was successfully treated with removal of the impacted denture from the left lower lobe bronchus by rigid bronchoscopy.